Structural and Functional Disruptions in Subcortical Vascular Mild Cognitive Impairment With and Without Depressive Symptoms - Lyu, Hanqing; Wang, Jianjun; Xu, Jinping; Zheng, Haotao; Yang, Xiaoyan; Lin, Songjun; Chen, Jianxiang; Zhou, Liuchang; Hu, Yuanming; Guo, Zhouke (Frontiers in Aging Neuroscience, 2019)
Many previous studies have revealed structural and functional abnormalities in patients with the subcortical vascular mild cognitive impairment (svMCI). Although depression symptoms were suggested to serve as a potential marker of conversion to dementia in patients with svMCI, whether these disruptions or other new findings will be identified in the svMCI comorbid with depression symptoms has not been established. In the current study, we combined voxel-based morphometry (VBM) and the resting state fMRI to investigate the structural and functional disruptions in the svMCI with and without depression symptoms using a cohort of 18 svMCI with depression symptoms (svMCI+D), 17 svMCI without depression symptoms (svMCI-D), and 23 normal controls (NC). As a result, we identified significantly decreased gray matter density in the left parahippocampus (ParaHIPP.L), the right hippocampus (HIPP.R), and the right middle cingulate cortex (MCC.R) in both svMCI+D and svMCI-D compared to NC. Most importantly, we also identified increased gray matter density in the MCC.R accompanied by increased resting state functional connectivity with ParaHIPP.R in the svMCI+D compared to svMCI-D. Moreover, the gray matter density of MCC.R and ParaHIPP.L was correlated with cognitive impairments and depression symptoms in the svMCI, respectively. In conclusion, these results extended previous studies and added weight to considerations of depression symptoms in the svMCI. Moreover, we suggested that a processing loop associated with HIPP, ParaHIPP, and MCC might be underlie the mechanism of depression symptoms in the svMCI.